2019
DOI: 10.7554/elife.45571
|View full text |Cite
|
Sign up to set email alerts
|

Club cells form lung adenocarcinomas and maintain the alveoli of adult mice

Abstract: Lung cancer and chronic lung diseases impose major disease burdens worldwide and are caused by inhaled noxious agents including tobacco smoke. The cellular origins of environmental-induced lung tumors and of the dysfunctional airway and alveolar epithelial turnover observed with chronic lung diseases are unknown. To address this, we combined mouse models of genetic labeling and ablation of airway (club) and alveolar cells with exposure to environmental noxious and carcinogenic agents. Club cells are shown to s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 58 publications
4
55
0
Order By: Relevance
“…Nevertheless, by leveraging MDS to study the mutagenesis process at the earliest stage of tumorigenesis, we detected the initiating Q 61 L/R mutations in Kras in the lungs of mice only days after exposure to urethane, capturing the very birth of cancer. We note that mutant allele-specific amplification 39,40 and droplet digital PCR 41 have documented Kras mutations after carcinogen exposure. However, we chose to develop MDS for the mammalian settings as these assays are either not as quantitative and sensitive 39,42 , or are designed to examine pre-selected mutations 41,43 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, by leveraging MDS to study the mutagenesis process at the earliest stage of tumorigenesis, we detected the initiating Q 61 L/R mutations in Kras in the lungs of mice only days after exposure to urethane, capturing the very birth of cancer. We note that mutant allele-specific amplification 39,40 and droplet digital PCR 41 have documented Kras mutations after carcinogen exposure. However, we chose to develop MDS for the mammalian settings as these assays are either not as quantitative and sensitive 39,42 , or are designed to examine pre-selected mutations 41,43 .…”
Section: Discussionmentioning
confidence: 89%
“…We note that mutant allele-specific amplification 39,40 and droplet digital PCR 41 have documented Kras mutations after carcinogen exposure. However, we chose to develop MDS for the mammalian settings as these assays are either not as quantitative and sensitive 39,42 , or are designed to examine pre-selected mutations 41,43 . Indeed, capitalizing on the ability of MDS to detect potentially any sequence variation in targeted regions of Ras genes at great sensitivity, we show at least three features underpinning the extreme mutational tropism of urethane-the mutational bias of this environmental carcinogen, transcription, and the gene locus.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study proves that the Sca-1 + Abcg1 + bronchioalveolar epithelial cells are the cancer stem cell-like subset of AT2 cells and are the origin of LADC in GPRC5A -knockout mice ( Yin et al., 2020 ). In addition to AT2 cells, Club cells are also shown to survive KRAS mutations and to form LADC after tobacco carcinogen exposure ( Spella et al, 2019 ). Bronchoalveolar stem cells (BASCs) can proliferate in vitro and are expanded at early stages of tumorigenesis in vivo following KRAS (G12D) mutation, suggesting that BASCs may be the cell of origin for LADC ( Kim et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the expression of SP-A protein is not limited to AT2 epithelial cells but also occurs in club cells. A recent study in mice has shown that adenocarcinomas may originate from club cells after exposure to smoke [129]. Aberrant processes in club cells may therefore promote tumourigenesis.…”
Section: Lung Cancermentioning
confidence: 99%